FEEDBACK IN THE SYSTEM OF STATE ADMINISTRATION - Gennadiy I. Koval'tsev (Вестник Российского экономического университета имени Г. В. Плеханова)
The article demonstrates multisided nature of the notion 'state administration'. The author puts forward a new definition for this category, which shows such important ideas as feedback, managerial work, administrative impact, power authorities. He analyzes the role and place of feedback in the process of state administration. The aim of feedback is getting information from the object of administration and delivering it to the entity of administration in order to do research within the frames of managerial work. The article puts forward suggestions aimed at developing state administration. First of all it means a new paradigm in relations between the object and entity of administration, wider use of 'sites' to provide feedback from the object of administration.